Acoustic vibration technology: Toward a promising fruit quality detection method. Issue 2 (15th February 2021) - Ding, Chengqiao; Feng, Zhe; Wang, Dachen; Cui, Di; Li, Weihao
Abstract: Understanding fruit quality is an effective way to reduce fruit loss and waste by providing proper strategies for fruit processing and management. Various noninvasive technologies have been developed for assessing fruit quality. Among them, acoustic vibration technology has received considerable attention from academics. As the fruit ripens, the physical and biochemical diversities of fruit cell lead to changes in the vibration characteristics of the fruit, which verified the feasibility of assessing fruit firmness by acoustic vibration technology from the microscopic view. Besides, the acoustic and vibration theories also provided the theoretical basis for this technology. The measurement system was mainly consisted of excitation devices, detection sensors, and signal processing modules. By using different excitation methods and devices, the fruit could demonstrate a free or forced vibration. The response signals of fruit were influenced by detection methods and sensors. To meet the requirement of high‐throughput detection, noncontact excitation devices and detection sensors were more suitable for on‐line applications. In addition, the relative locations of excitation and detection points and the posture style of fruit also had an impact on the measurement results, which should be determined before the test. Moreover, the proper data analysis method was equally important to extract potential parameters to improve the performance of prediction models. This paper provided a comprehensive overview concerning the principle, system composition, data analysis, and on‐line applications of acoustic vibration technology, and discussed the perspectives of future trends to promote the intensive study and further extension of this technology.